Література та культура Полісся. Вип. 81 - (:unkn) unknown (My University, 2016)
Literature and Culture of Polissya. – Vol. 81. Series "History Research". – № 4 / editor-in-chief H. V. Samoylenko. – Nizhyn : NDU named after Gogol, 2016. – 241 p.